Effect of plant growth-promoting bacteria (PGPB) on the antioxidant and antibacterial activities in Chilean ‘sapito’ common beans - Nicolás Flores-Castañón; Cynthia Meza; Francisca Valenzuela; Catherine Ormeño; Jaime Tapia; Basilio Carrasco; Aparna Banerjee (BMC Plant Biology)
Abstract Common beans (Phaseolus vulgaris L.) are a nutritionally valuable crop with high levels of bioactive compounds, including phenolics with antioxidant and antibacterial properties. However, the functional potential of local Chilean landraces remains underexplored. Plant growth-promoting bacteria (PGPB) can influence plant metabolism, enhancing the accumulation of secondary metabolites. This study evaluates the effect of PGPB (Bacillus proteolyticus Cyn1, Bacillus safensis Cyn2, and their consortium) on the total phenolic content (TPC), antioxidant capacity, and antibacterial activity of extracts from the Chilean landrace ‘Sapito’. For this, ‘Sapito’ bean seeds were inoculated with individual PGPB strains and their consortium and cultivated under field conditions. Extracts from the seed coat and cotyledons were obtained using water, ethanol, and acetone. TPC was determined using the Folin–Ciocalteu method, antioxidant activity was assessed via DPPH, ABTS, H₂O₂ scavenging, ferrous ion chelation, and FRAP assays, while antibacterial activity was evaluated through agar diffusion, growth inhibition, and cell viability assays against Gram positive Bacillus cereus and Gram negative Pseudomonas putida. PGPB inoculation significantly influenced TPC, with consortium-treated seeds accumulating higher phenolic content in aqueous extracts (95.9 ± 27.8 mg GAE/100 g dry seed). Antioxidant activity varied across treatments and solvents, with ethanolic and acetone extracts displaying the highest radical scavenging activities. Antibacterial assays revealed that ethanolic seed coat extracts exhibited stronger inhibition against B. cereus. In conclusion, this is the first study evaluating the impact of PGPB on the functional properties of a Chilean common bean landrace. The findings highlight the potential of microbial inoculation to enhance phenolic accumulation and bioactivity, supporting sustainable agriculture, food security, and germplasm conservation in the face of climate change.